PENERAPAN CI (CODE IGNITER) UNTUK PENJUALAN BATU DI DESA SENGKUANG (STUDI KASUS CV QUARI SENGKUANG) - fiqri maulana; Pahrizal Pahrizal; Harry Witriyono (UNIVED Press, 2022)
Abstract—The business world will always develop along with the times, with various kinds of technology that are so sophisticated and diverse that the competition in the business world is getting tougher. The business world engaged in stone sales has a lot of bookkeeping because the bookkeeping is carried out every day, such as administrative bookkeeping carried out by the cashier when recording sales transactions with buyers and also inventory data bookkeeping carried out by the factory section which records inventory. In the research conducted for the development of a web-based sales transaction application using the Code Igniter framework. Code Igniter is one of the widely used frameworks, where the main goal is to minimize code during website creation. So that CV Quari Sengkuang can apply the concept of inventory control which is defined as the number or quantity of goods ordered with minimal costs or often referred to as the optimal purchase amount. Keywords: Stone, Codeigniter, Implementation, Website